ErbB3 binding protein 1 (EBP1) participates in the regulation of intestinal inflammation via mediating Akt signaling pathway. Issue 2 (October 2015) - Miao, Xianjing; Tang, Qiyun; Miao, Xiaobing; Wu, Yaxun; Qian, Ji; Zhao, Weijuan; Wang, Liang; Li, Liren; Zhang, Dongmei
Highlights: In this article, we established the DSS-induced colitis mouse model of acute colitis, recovery from acute intestinal inflammation, and chronic colitis. This text for the first time that EBP1 was down-regulated in intestinal epithelial cell (IECs) of patients with UC. EBP1 may participate in the regulation of intestinal inflammation via regulating the activation of Akt signaling pathway. Abstract: ErbB3 binding protein-1 (EBP1) belongs to a family of DNA/RNA binding proteins implicated in cell growth, differentiation and apoptosis. Previous data demonstrated that EBP1 regulates phosphorylation of Akt to drive tumor progress. However, the expression and biological functions of EBP1 in ulcerative colitis (UC) remain unclear. In this study, we reported for the first time that EBP1 was down-regulated in intestinal epithelial cell (IECs) of patients with UC. In DSS-induced colitis, we observed the down-regulation of EBP1 accompanied with the elevated levels of proinflammatory cytokines (IL-1β, IL-6 and IL-8) and Akt activation indicators (phosphorylated Akt) in colitis IECs, indicating the possible involvement of EBP1 in regulation of intestinal inflammation via mediating Akt in UC. Employing the TNF-α-treated HT-29 cells as an IEC inflammatory model, we confirmed the negative correlation of EBP1 with Akt activation and Akt-dependent inflammation progress in vitro . EBP1 knocking down and over-expression significantly regulated TNF-α-induced Akt activation and proinflammatory cytokines expression in HT-29 cells. Taken together, our data suggested that EBP1 participates in the regulation of intestinal inflammation via mediating Akt signaling pathway.